Static and dynamic characteristics of externally pressurized gas bearing for high-speed hydrogen turbo-expander. Issue 1 (1st May 2022) - Yan, H; Ke, C L; Peng, N; Li, K R; Zhang, X H; Zheng, L W; Liang, Y W; Xiong, L Y; Dong, B; Li, J; Liu, I Q
Abstract: The high-speed hydrogen turbo-expander, serves as a key component of the large-scale hydrogen liquefaction system, receives a lot of attention. Being an essential part of the turbo-expander, gas bearings are widely used for its pollution-free and low viscosity advantages. However, studies on characteristics of hydrogen bearing, especially on the static and dynamic characteristics of externally pressurized hydrogen journal bearing, have not been conducted by many. Here, the finite difference method (FDM) was employed to solve the Reynolds equation thus obtaining the pressure distribution and the static load capacity. The partial derivative method (PDM) was used to calculate the dynamic stiffness coefficients and damping coefficients of hydrogen bearing. The critical mass was used to analyze the linear instability of the hydrogen bearing-rotor system. Relationship between various design parameters, including eccentricities, orifice diameter, clearance, supply pressure and rotor speeds, and static and dynamic behaviours of hydrogen bearing has been established. The results indicate that load capacity increase and volume flow rate decrease is viable through parameter optimization. The stability of the hydrogen bearing-rotor system is evaluated quantitatively.